Sympathy for the digital: Influence of synthetic voice on affinity, social presence and empathy for photorealistic virtual humans - Higgins, Darragh; Zibrek, Katja; Cabral, Joao; Egan, Donal; McDonnell, Rachel (Computers & graphics, 2022)
In this paper, we investigate the effect of a realism mismatch in the voice and appearance of a photorealistic virtual character in both immersive and screen-mediated virtual contexts. While many studies have investigated voice attributes for robots, not much is known about the effect voice naturalness has on the perception of realistic virtual characters. We conducted the first experiment in Virtual Reality (VR) with over two hundred participants investigating the mismatch between realistic appearance and unrealistic voice on the feeling of presence, and the emotional response of the user to the character expressing a strong negative emotion. We predicted that the mismatched voice would lower social presence and cause users to have a negative emotional reaction and feelings of discomfort towards the character. We found that the concern for the virtual character was indeed altered by the unnatural voice, though interestingly it did not affect social presence. The second experiment was conducted with a view towards heightening the appearance realism of the same character for the same scenarios, with an additional lower level of voice realism employed to strengthen the mismatch of perceptual cues. While voice type did not appear to impact reports of empathic responses towards the character, there was an observed effect of voice realism on reported social presence, which was not detected in the first study. There were also significant results on affinity and voice trait measurements that provide evidence in support of perceptual mismatch theories of the Uncanny Valley. [Display omitted] •Text-to-speech voice measured to influence social presence and appeal.•No influence of voice on reports of empathy.•Natural voice measured most consistent and appealing.